Prevention of ventilator-associated pneumonia with probiotics: an overview of systematic reviews - Han, Minjuan; Wang, Ke; Sun, Lei; Liu, Wang; Dong, Wanhu (Frontiers in Microbiology, 2024)
Background: Probiotics has been used as an adjuvant therapy for the prevention of ventilatorassociated pneumonia (VAP). This study aimed to systematically compile, evaluate, and synthesize previous systematic reviews (SRs) and meta-analyses (MAs) on the prevention of VAP with probiotics. Methods: The methodological quality, reporting quality, and evidence quality of enrolled studies were respectively evaluated by Assessment of Multiple Systematic Reviews 2 (AMSTAR-2) tool, Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklists, and Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) system. Results: Thirteen eligible publications were analyzed in this overview. The included studies were rated as generally low methodological quality owing to the lack of a registered protocol or a list of exclusion criteria. The inadequate quality of the reports was demonstrated by the lack of reporting on the registration protocols, the lack of reporting on the search strategy, and the lack of reporting on the additional analyses. For GRADE, there were 36.17% (17/47) outcomes graded to be of moderate quality, 42.55% (20/47) to be of low quality, and 21.28% (10/47) to be of very low quality. Conclusions: Probiotics may be associated with reduced incidence of VAP. However, caution should be exercised when recommending probiotics for the prevention of VAP owing to the poor quality of the current evidence.